The Pathophysiology of Low Systemic Blood Flow in the Preterm Infant - Kluckow, Martin (Frontiers in Pediatrics, 2018)
Assessment and treatment of the VLBW infant with cardiovascular impairment requires understanding of the underlying physiology of the infant in transition. The situation is dynamic with changes occurring in systemic blood pressure, pulmonary pressures, myocardial function, and ductal shunt in the first postnatal days. New insights into the role of umbilical cord clamping in the transitional circulation have been provided by large clinical trials of early versus later cord clamping and a series of basic science reports describing the physiology in an animal model. Ultrasound assessment is invaluable in assessment of the physiology of the transition and can provide information about the size and shunt direction of the ductus arteriosus, the function of the myocardium and its filling as well as measurements of the cardiac output and an estimate of the state of peripheral vascular resistance. This information not only allows more specific treatment but it will often reduce the need for treatment.